Moral injury in secure mental healthcare: part I: exploratory and confirmatory factor analysis of the Moral Injury Events Scale - Morris, Deborah J. (The journal of forensic psychiatry & psychology, 2022)
In recognition that existing theoretical paradigms may not offer a comprehensive account of the range of occupational stressors and responses experienced by healthcare professionals, interest in moral injury has grown. The Moral Injury Events Scale (MIES) remains the dominant assessment tool used to measure potentially morally injurious experiences (PMIEs) across different occupational groups, including healthcare professionals. Given the proliferation of research using the MIES in healthcare, in the context of ongoing debates about its structure and utility, an exploration of the psychometric properties of the MIES with this population is timely. Using the data (N = 235) from a study exploring the prevalence of exposure to PMIEs, the current study reports on the factor structure of the MIES in healthcare professionals working within a secure mental health setting. The results yielded a two-factor model representing transgressions and betrayals by ‘others’, and transgressions committed by the ‘self’. Exploration of the internal consistency of the scale yielded a McDonald’s ω of .93. Multi-group confirmatory factor analysis highlighted the model was an adequate fit for White females, tentatively suggesting that experiences of moral injury may vary by gender, intersected by ethnicity. Accordingly, future frameworks, measures and interventions to remediate the impact of moral injury may require an intersectional approach.